Influence of Microstructure on the Corrosion Resistance of Low Carbon Uns S41003 Stainless Steel - L.F. Guedes; E.A. Ponzio; V.M. Santos; A.R. Pimenta; S.S.M. Tavares (Materials Research)
The UNS S41003 (ASTM A1010) is a lean stainless steel with a chromium content of 10.5-11.0%. Its relatively low cost and enhanced corrosion resistance make it a promising alternative to carbon steels in various applications. Depending on the processing route the UNS S41003 with low carbon (<0.02%) and small Ni addition (~0.30%) may present ferritic, martensitic or ferritic-martensitic microstructures. In this work the corrosion resistance was evaluated in specimens processed by three different ways: hot rolling (HR), batch annealing (ANN), and water quenching from 1000ºC (Q). The microstructure of the HR is majoritarily martensitic, but also contains delta (δ) ferrite and fine dispersed carbides. The ANN specimen has equiaxial α ferritic grains with intergranular Cr carbides, and the quenched (Q) was martensitic. Polarization curves were carried out in 0.1M HCl solution. DL-EPR tests were also performed to evaluate the intergranular corrosion susceptibilities. It was observed that the martensitic microstructures have better corrosion than the annealed steel in polarization tests. which was highly susceptible to intergranular attack due to sensitization caused by intergranular Cr carbides.